Growing grassroots innovations: Exploring the role of community-based social movements for sustainable energy transitions - Gill Seyfang; Alex Haxeltine (University of East Anglia, The Centre for Social and Economic Research on the Global Environment (CSERGE), 2010)
The challenges of sustainable development (and climate change and peak oil in particular) demand system-wide transformations in socio-technical systems of provision. An academic literature around co-evolutionary innovation for sustainability has recently emerged to attempt to understand the dynamics and directions of such socio-technical transformations and social change, which are termed 'sustainability transitions'. This literature has previously focused on market-based technological innovations. Here we apply it to a new context of social movements and social innovation, and examine the role of civil society-based social movements in a transition to a low-carbon sustainable economy in the UK. We present new empirical research from a study of the UKs Transition Movement (a 'grassroots innovation') and assess its attempts to grow and diffuse beyond the niche. Applying strategic niche management theory to this civil society context delivers theoretically-informed practical recommendations for this social movement to diffuse beyond its niche: to foster deeper engagement with resourceful regime actors; to manage expectations more realistically by delivering tangible opportunities for action and participation; and to embrace a community-based, action-oriented model of social learning (in preference to a cognitive theory of behaviour change). Furthermore, our study indicates areas where theory can be refined to better explain the experience of grassroots innovations and social movements, namely through a fuller appreciation of internal niche processes, and integration with theories of social movements and social practices.
Keywords: 330; sustainable consumption; energy; social movements; sustainability transitions; social innovation; socio-technical systems; Umweltbelastung; Energieversorgung; Nachhaltigkeit; Lernen; Gesellschaft; Soziale Bewegung; Großbritannien; Norwegen